Integrasi Nilai-Nilai Huma Betang dalam Pendidikan Ekonomi: Membangun Ekonomi Inklusif dan Berkelanjutan Berdasarkan Kearifan Lokal Masyarakat Dayak - Arna Purtina (FKIP Unswagati, 2026)
This research is based on the importance of integrating local wisdom in character building and sustainable economic management among Dayak communities, particularly in the context of Huma Betang. The purpose of this study is to examine how Huma Betang values, such as togetherness, honesty, equality, and tolerance, can be integrated into economic education, with a focus on inclusive and sustainable economic development based on local wisdom. Using a qualitative descriptive and phenomenological approach, this study involved in-depth interviews, participant observation, and documentation data collection conducted in Bontoi Village, Central Kalimantan. The results of this study indicate that Huma Betang values ​​are not only relevant in social life but can also strengthen the economic education curriculum. The application of these values ​​can help students understand business ethics, collaboration, and diversity, as well as foster strong character to face global economic challenges. This study recommends further exploration of the application of local wisdom values ​​in economic education in various cultural communities, to support more equitable, inclusive, and sustainable economic development. Kata Kunci: Huma Betang, Nilai Budaya, Pendidikan Ekonomi, Kearifan Lokal, Keberlanjutan